2010
DOI: 10.1007/s10611-010-9254-5
|View full text |Cite
|
Sign up to set email alerts
|

Prison privatization: a perspective on core governmental functions

Abstract: Prison privatization in the US illustrates the challenge of privatization to the traditional state monopoly over "inherently governmental" functions. From a perspective on core governmental functions, this paper provides a new logical explanation of this phenomenon and argues that prison privatization demonstrates the political rationality of governments. Conservative social control and economic neoliberalism were two major political reasons for prison privatization in the US. These factors aggravated the inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
(32 reference statements)
0
16
1
2
Order By: Relevance
“…Other factors closely associated with partisan politics, however, are important. Numerous study results have indicated a link exists between political ideology (liberalism) of a state and its privatization policy (Burkhardt, ; Jing, ; Nicholson‐Crotty, ). Others have shown a negative relationship between union membership (itself a historical force in Democratic politics) and prison privatization (Burkhardt, ; Gunderson, ).…”
Section: Politics Influence Privatizationmentioning
confidence: 99%
“…Other factors closely associated with partisan politics, however, are important. Numerous study results have indicated a link exists between political ideology (liberalism) of a state and its privatization policy (Burkhardt, ; Jing, ; Nicholson‐Crotty, ). Others have shown a negative relationship between union membership (itself a historical force in Democratic politics) and prison privatization (Burkhardt, ; Gunderson, ).…”
Section: Politics Influence Privatizationmentioning
confidence: 99%
“…Whereas traditional penology stems from criminal law and criminality that has emphasized punishing and correcting individual offenders, the new penology adopts an actuarial approach in which specialists assess the risks of specific criminal subpopulations (p. 74). This new penology corresponds with and reinforces one of the most profound changes in the prison system, and in particular, the system of incarcerating immigrants: the privatization of prisons (Jing, 2010). As part of the global trend of neoliberal state policies designed to turn services previously handled by government over to the market (Dominelli, 2010), the privatization of prisons has accelerated rapidly.…”
Section: Introductionmentioning
confidence: 71%
“…Though historically private sector involvement in corrections dates back to the eighteenth century, it was not until the early 1980s that the USA saw private companies contracting with state governments to operate correctional facilities (Jing, 2010). The Corrections Corporation of America (CCA) began operations in 1983 under the premise that private industry could provide cost savings to federal, state, and local governments through public-private prison partnerships.…”
Section: Privatization Profit and Immigration Detention Centersmentioning
confidence: 99%
“…This is not surprising given that politics have been found to influence SPP decisions. States exuding higher levels of mass conservatism are more amendable to SPP arrangements and are more likely to “favor neoliberal economic policies” (Jing , 268). We also find that the competitive influence of neighboring SPP adoption on home state adoption is dampened significantly in relatively liberal state contexts, suggesting that a state's political orientation moderates the relationship between neighboring SPP adoptions and likelihood of home state adoption.…”
Section: Discussionmentioning
confidence: 99%